Early Childhood Caries Prevalence and Associated Risk Factors in Monastir, Tunisia: A Cross-Sectional Study - Chouchene, Farah; Masmoudi, Fatma; Baaziz, Ahlem; Maatouk, Fethi; Ghedira, Hichem (Frontiers in Public Health, 2022)
Purpose The present study aimed to investigate the prevalence and risk factors of ECC among preschool children in Monastir, Tunisia. Methods The survey was designed as a cross-sectional study carried out between February and April 2021 in the main region of Monastir, Tunisia. A total of 381 preschool children were randomly selected using a three-stage clustered sampling technique from 10 daycares. The dental caries were diagnosed using WHO recommendations and a questionnaire in Arabic language was used to record personnel profile of the enrolled children. The chi-square test was used in bivariate analyses to assess the association between ECC and risk factors. Variables showing significant associations were included in multiple logistic regression models. Results The prevalence of ECC was 20% and the mean dmft score was 0.89 ± 0.24. The prevalence of ECC increased at the age of 48–59 months ([OR] 2.602; 95%CI: 1.122–2.302), the age of 60–71 months ([OR] 2.845; 95% CI: 1.128–2.072), in children with nocturnal feeding ([OR] 2,417; 95% CI: 1.340–4,358), who take sugary drinks in the bottle ([OR] 1.104; 95% CI: 1.667–2.826), stopped breast or bottle feeding after the age of 18 months ([OR] 2.417; 95% CI: 1.340–4.358), do not brush their teeth properly ([OR] 1.435; 95% CI: 1.207–2.915), had visited a dentist ([OR] 2.444; 95% CI: 2.072–1.108), and decreased in children with a more highly educated parents ([OR] 0.797; 95%CI: 0.171–0.650). Conclusion Given the relatively high prevalence of ECC in Tunisia, it is important to review public dental health policies and develop effective strategies to encourage changes in behavior related to the oral health of children to prevent the spread and worsening of this disease.